PERAN KOPERASI DALAM PEREKONOMIAN INDONESIA TERHADAP HUKUM PENANAMAN MODAL - Florentinus Sudiran (Universitas 17 Agustus 1945 Samarinda, 2018)
The aim of this research ie to know the role of the Coeperation inIndonesian economy in 2017. The methode of it library one by taking thedata from magzine, daily newpaper, goggle and others. The results of itare (1) Cooperation is business body which the members of people or laworgnization based the priciples of cooperation and automtically themovement people economy based on as the priciple of family group, (2)The cooperation has the big role in the aindonesian economy bacause itcan dinamize the people economi, (3) The situation of the cooperation isvery stratagic it is, threfore, the government takes vocus in the nationaleconomic development, (3) At themoment it is badly needed the strongcommitment to develop cooperation which is able to help itself accordingto its identity of it. The suggestions are (1) The government can support ittowards the global economy; (2) By global it can more active to developIndonesian economy maximallyand can improve the society welfare